Transformasi Media Dakwah: Pelatihan Content Creator di Lingkungan Pesantren Al Hikmah Permata Kajen - Fajar Adhi Kurniawan; Hasan Labiqul Aqil; Ummi Durrotun Niha; M. Agus Zainal Mahasin; Aksa Aksa (LPPI UMN AL WASHLIYAH, 2025)
Changes in media consumption patterns have forced Islamic boarding schools, as Islamic educational institutions, to adapt their preaching methods to utilize digital technology. This community service program aims to train students at the Al Hikmah Kajen Islamic Boarding School to become content creators capable of producing high-quality content for digital platforms. Using the Participatory Learning Approach (PLA), the training involves 35 students aged 13-18, covering scriptwriting, photography, graphic design, and camera-speaking techniques. The training results demonstrate an improvement in participants' technical skills in producing content such as monologue videos, podcasts, and tutorials. Students are expected to be able to utilize digital media as an effective means of da'wah. This program also strengthens the pesantren's branding in the digital world. The training demonstrates that integrating technology with da'wah values can have a significant impact in empowering students and expanding the reach of the pesantren's da'wah efforts. Keywords: Media da’wah, pesantren, digital literacy